A novel coil array for combined TMS/fMRI experiments at 3 T. Issue 5 (24th November 2014) - Navarro de Lara, Lucia I.; Windischberger, Christian; Kuehne, Andre; Woletz, Michael; Sieg, Jürgen; Bestmann, Sven; Weiskopf, Nikolaus; Strasser, Bernhard; Moser, Ewald; Laistler, Elmar
<x xml:space="preserve">Abstract</x> Purpose To overcome current limitations in combined transcranial magnetic stimulation (TMS) and functional magnetic resonance imaging (fMRI) studies by employing a dedicated coil array design for 3 Tesla. Methods The state‐of‐the‐art setup for concurrent TMS/fMRI is to use a large birdcage head coil, with the TMS between the subject's head and the MR coil. This setup has drawbacks in sensitivity, positioning, and available imaging techniques. In this study, an ultraslim 7‐channel receive‐only coil array for 3 T, which can be placed between the subject's head and the TMS, is presented. Interactions between the devices are investigated and the performance of the new setup is evaluated in comparison to the state‐of‐the‐art setup. Results MR sensitivity obtained at the depth of the TMS stimulation is increased by a factor of five. Parallel imaging with an acceleration factor of two is feasible with low g‐factors. Possible interactions between TMS and the novel hardware were investigated and were found negligible. Conclusion The novel coil array is safe, strongly improves signal‐to‐noise ratio in concurrent TMS/fMRI experiments, enables parallel imaging, and allows for flexible positioning of the TMS on the head while ensuring efficient TMS stimulation due to its ultraslim design. Magn Reson Med 74:1492–1501, 2015. © 2014 The Authors. Magnetic Resonance in Medicine published by Wiley Periodicals, Inc. on behalf of International Society for Magnetic Resonance in Medicine.